PENERAPAN MODEL PICTURE AND PICTURE PADA MATERI GANGGUAN KESEHATAN PADA ORGAN PEREDARAN DARAH DAPAT MENINGKATKAN HASIL BELAJAR SISWA DI KELAS V SD NEGERI TEUREUBUE - Nasri Diana (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2021)
This study aims to determine the improvement of student learning outcomes in class V SD Negeri Tereubue by applying the picture and picture model to the lesson disturbances in blood circulatory organs. The type of research was Classroom Action Research. The subjects of the research were 5th grade, totaling 19 students consisting of 14 boys and 5 girls. Data collection techniques used LKS, LOAS, LOAG, and test questions. The study consisted of 3 cycles. In the first cycle, the average score of students was 66.31 with a completeness percentage of 46.36%. In the second cycle increased with the average value of students is 76.56 with a percentage of completeness of 89.47%. Furthermore, there was a significant increase in cycle III with the acquisition of an average score of 85.53 students with a percentage of completeness of 100%.